Investigating the inflammatory effect of microplastics in cigarette butts on peripheral blood mononuclear cells - Monire Soltani; Abbas Shahsavani; Philip K. Hopke; Nadali Alavi Bakhtiarvand; Mehrnoosh Abtahi; Masoumeh Rahmatinia; Majid Kermani (Scientific Reports)
Abstract Cigarette filter microplastics are composed of cellulose acetate that does not undergo biological or photo-degradation. These microplastics are readily dispersed and can be found abundantly in water, soil, and air. These fibers possess high absorption capabilities, allowing them to collect and retain pollutants such as toxic elements. As a result, they are regarded as potential dangers to living organisms. The purpose of this study was to analyze the immune response of human peripheral blood mononuclear cells (PBMCs) when exposed to cigarette filter microfibers, measuring the secretion of the inflammatory cytokines TNFα (tumor necrosis factor-alpha) and IL-6 (interleukin-6). In this study, we examined how used cigarette cellulose acetate microfibers affect the viability of peripheral blood mononuclear cells in an appropriate culture medium at three concentrations: 50, 100, and 200 µg/ml. In addition, this study investigated the release of inflammatory cytokines TNFα and IL6 from PBMCs exposed to 200 µg/ml cigarette filter cellulose acetate. The results showed that increasing the concentration of cellulose acetate fibers of one of the brands in the culture medium has a significant effect on reducing cell viability. The 200 µg/ml in DW is more effective than 50 and 100 µg/ml in reducing cell viability. Peripheral blood mononuclear cells showed an inflammatory immune response when exposed to 200 µg/ml cellulose acetate from cigarette filters. They produced inflammatory cytokines that showed a significant increase compared to the control sample. In general, it can be concluded that cellulose acetate fibers in contact with body cells stimulate them and cause an inflammatory response.